Über die Notwendigkeit der Historischen Bildungsforschung Wegbegleiter*innenschrift für Edith Glaser - Thole, Friederike; Wedde, Sarah; Kather, Alexander (Verlag Julius Klinkhardt, 2021)
For a long time, historical educational research has seen a decline in its representation in university teaching and academic posts. Concurrently, its thematic and methodological variation has expanded impressively in the last two decades. This volume, dedicated to Edith Glaser, aims to enrich the legitimacy discourse on the importance and necessity of educational historical expertise from two perspectives. On the one hand, it presents exemplary fields of research in the history of education, on the other hand, contributions show the relevance of historical educational research for other (sub-)disciplines.